PENGARUH MANAJEMEN LAPORAN KEUANGAN KONSOLIDASIAN TERHADAP NILAI PERUSAHAN PT. ACE HARDWARE INDONESIA Tbk - Kurnia, Aini; Amaro, Ceisya; Thalia, Alinda; Ratiyah, Ratiyah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2024)
The purpose of this research is to determine the influence of consolidated financial report management on the value of PT. ACE Hardware Indonesia Tbk for the period 2021-2023 listed on the Bursa Efek Indonesia (BEI). The consolidated financial position report of the company, which describes the parent entity and its subsidiaries as an economic unit in terms of assets, liabilities, equity, income, expenses, and cash flows, is known as the consolidated financial report. The data used in this research is secondary data in the form of financial reports processed using quantitative analysis and descriptive statistics methods. Meanwhile, the secondary data was obtained through the population, and the sample used is the ratio of the consolidated financial position report of PT. ACE Hardware Indonesia Tbk for the period 2021-2023 listed on the Bursa Efek Indonesia (BEI). This research investigates how consolidated financial report management and the value of PT. ACE Hardware Indonesia Tbk during the period 2021-2023 influence each other, which is done using the company's consolidated financial data and appropriate analysis techniques. In analyzing the data, descriptive statistical analysis methods and quantitative analysis methods are used. The calculations in this research use liquidity ratios, namely Current ratio, quick ratio, and Cash ratio. While the solvency ratio calculations include Debt to asset ratio and Debt to equity ratio. For profitability calculations, Gross profit margin ratio, Net profit margin ratio/profit margin, ROE, and ROA are considered. The research is expected to provide a deeper insight into strategic and efficient ways to integrate financial reports to enhance the company's value. This study can help companies optimize their financial management strategies for better performance and increased company value.